The Influence Of Communication, Motivation And Work Environment On Employees’ Performance At The Department Of Fire Fighting And Rescue Office Of Bengkulu City - Febrianto, Edy; Wijaya, Ermy; Utama Putra, Iswidana (Jurnal Pakar Manajemen, 2024)
The purpose of this research is to find out whether communication, motivation and work environment influence employees’ performance at the Department of Fire Fighting and Rescue Office of Bengkulu City. This type of research is a type of quantitative descriptive research. The data collection method in this research uses observation and questionnaire techniques, with a sample of 70 respondents. The results of the research show that multiple linear regression Y = 55.101+ 0.271 X1+ 0.196 X2 + 0.257 X3) on employees’ performance at the Department of FireFighting and Rescue Office of Bengkulu City. The results show that the communication test (XI) shows t count 3.504 > t table 1.666 and significance 0.001 <0.05, meaning that communication (XI) has a positive and significant effect on employees’ performance at the Department of Fire Fighting and Rescue Office of Bengkulu City. The results of the motivation test (X2) show t count 1.708 > t table 1.666 and significance 0.002 <0.05, so the results of the hypothesis Ha are accepted and Ho is rejected, meaning that motivation (X2) has a positive and significant effect on employee performance at the Department of Fire Fighting and Rescue Office of Bengkulu City. The results of the work environment test (XI) show t count 2.277 > t table 1.666 and significance 0.006 <0.05, so the results of Ha is accepted and Ho is rejected, meaning that the environment (XI) has a positive and significant effect on employees’ performance at the Department of Fire Fighting and Rescue Office of Bengkulu City. The result of Fcount is greater than F table, namely 5.906 > 2.74, so it is concluded that the Hypothesis is Accepted, meaning that there is a simultaneous influence between communication (XI) and motivation (X2) and the work environment (X3) on employee performance (Y) at the Department of Fire Fighting and Rescue Office of Bengkulu City. This can be seen at the significance level of 0.001 < 0.05.